2009
DOI: 10.3945/ajcn.2008.27416
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for childhood obesity and metabolic dysregulation

Abstract: Background: Childhood obesity has increased significantly in recent decades. Objective: The objective was to examine the perinatal risk factors related to childhood obesity. Design: In a prospective study, 89 women with normal glucose tolerance (NGT) or gestational diabetes mellitus (GDM) and their offspring were evaluated at birth and at 8.8 6 1.8 y. At birth, obstetrical data, parental anthropometric measures, and neonatal body composition were assessed; at follow-up, diet and activity were assessed and labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
399
5
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(431 citation statements)
references
References 34 publications
19
399
5
8
Order By: Relevance
“…These diseases are due to multifactorial causes that include genetic and environmental factors (O'Rahilly et al, 2005). Human epidemiological and animal experimental studies indicate that alteration in fetal growth and development in response to prenatal environmental conditions such as nutritional stimulus may have deleterious persistent health effects lasting for the entire life (Wu et al, 2004;Catalano et al, 2009). Researches have demonstrated a link between maternal malnutrition and offspring risk of metabolic diseases (Barker et al, 1993;Tappia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are due to multifactorial causes that include genetic and environmental factors (O'Rahilly et al, 2005). Human epidemiological and animal experimental studies indicate that alteration in fetal growth and development in response to prenatal environmental conditions such as nutritional stimulus may have deleterious persistent health effects lasting for the entire life (Wu et al, 2004;Catalano et al, 2009). Researches have demonstrated a link between maternal malnutrition and offspring risk of metabolic diseases (Barker et al, 1993;Tappia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, hyperleptinemia during neonatal life may program leptin resistance via dual effects on food intake and energy expenditure, with long-term adverse consequences for the hypothalamic circuits regulating energy balance (2,35). Some studies have shown an increased risk for obesity and insulin resistance in neonates born to obese mothers, as well as higher levels of leptin and markers of inflammation than in infants born to lean mothers (36).…”
Section: Pregnancy and Intrauterine And Neonatal Developmentmentioning
confidence: 99%
“…1 Risk factors for obesity start to accrue even in fetal life and include maternal obesity 2 and slow or fast fetal growth. 3 Preterm birth itself has been variably associated with later onset of metabolic disorders related to obesity such as insulin resistance and hypertension.…”
Section: Introductionmentioning
confidence: 99%